Comprehensive Physiology 2013
DOI: 10.1002/cphy.c120034
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Genes to Endothelial Cells and Cell‐ and Gene‐Based Therapy in Pulmonary Vascular Diseases

Abstract: Pulmonary arterial hypertension (PAH) is a devastating disease that, despite significant advances in medical therapies over the last several decades, continues to have an extremely poor prognosis. Gene therapy is a method to deliver therapeutic genes to replace defective or mutant genes or supplement existing cellular processes to modify disease. Over the last few decades, several viral and nonviral methods of gene therapy have been developed for preclinical PAH studies with varying degrees of efficacy. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 250 publications
0
13
0
Order By: Relevance
“…Thus, an adjunctive therapy that could directly address and attenuate severe occlusive arteriopathy is greatly needed. This rationale has been the basis for studies of gene- and cell-based therapies in animal models of PAH [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an adjunctive therapy that could directly address and attenuate severe occlusive arteriopathy is greatly needed. This rationale has been the basis for studies of gene- and cell-based therapies in animal models of PAH [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current therapeutic approaches aim to prevent further pulmonary damage by using parenteral, inhaled, and oral combinations of prostaglandins (e.g., prostanoids), endothelin receptor antagonists, diuretics, calcium channel blockers, and phosphodiesterase-5 inhibitors (19,112,134). Hopes of reversing established PAH via regenerative approaches, including the use of endothelial progenitor cells and mesenchymal stem cells, await extensive clinical testing (155). Riociguat is a soluble guanylate cyclase stimulator that belongs to a new class of vasodilators currently in clinical development, which reversed right heart hypertrophy and ventricular remodeling associated with PAH in rats and mice (5).…”
Section: Hiv-associated Challenges In the Lungmentioning
confidence: 99%
“…Recent understanding of the role of adult stem and progenitor cells in the maintenance of vascular homeostasis and repair of injury has stimulated interest in the potential for regenerative cell therapies for PAH. Most of the preclinical studies of cell therapy for PAH have used two cell types in particular, early-outgrowth endothelial progenitor cells (EPCs, also known as circulating angiogenic cells, myeloid angiogenic cells) and mesenchymal stromal cells (MSCs, also known as mesenchymal stem cells, adult stem cells) [ 8 , 9 ]. EPCs and MSCs have been described as dynamic and responsive cells that can migrate to sites of vascular injury in several in vivo animal disease models [ 10 ], facilitating neovascularization and reducing inflammation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the preclinical studies of cell therapy for PAH have used two cell types in particular, early-outgrowth endothelial progenitor cells (EPCs, also known as circulating angiogenic cells, myeloid angiogenic cells) and mesenchymal stromal cells (MSCs, also known as mesenchymal stem cells, adult stem cells) [ 8 , 9 ]. EPCs and MSCs have been described as dynamic and responsive cells that can migrate to sites of vascular injury in several in vivo animal disease models [ 10 ], facilitating neovascularization and reducing inflammation [ 8 ]. As a treatment for PAH, preclinical studies involving these cell types have demonstrated efficacy in improving key pathological features of PAH such as cardiopulmonary hemodynamics, restoring the degenerated microvascular area, and reducing both right ventricular and pulmonary vascular remodeling [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation